755 Research priorities for prehospital care of older patients with injuries: scoping review. Issue 3 (21st February 2022) - Harthi, Naif; Goodacre, Steve; Sampson, Fiona; Alharbi, Rayan
Abstract : Introduction and purpose: The use of ambulance services by older patients with injuries increases within the impacts of ageing-related changes leading to adverse patient outcomes. There is increasing recognition of the importance of prehospital trauma care for older patients, but little systematic research to guide practice. We aimed to review the published evidence on prehospital trauma care for older patients, determine the scope of existing research and identify research gaps in the literature. Methods: A systematic scoping review guided by the Arksey and O'Malley framework reported in line with the PRISMA-ScR checklist. A systematic search was conducted of Scopus, CINAHL, MEDLINE, PubMed and Cochrane library databases to identify articles published between (2001–2021) years. Inclusion and exclusion criteria were applied independently by two reviewers. Data were extracted, charted and summarised from eligible articles. Results: 65 studies were identified and reviewed, and 25 included. Five categories were identified: 'field triage, 'ageing impacts', 'decision-making', 'paramedic' awareness' and 'paramedic's behaviour'. Undertriage & overtriage (sensitivity & specificity) were commonly cited as poorly investigated field-triage subthemes. Ageing-related physiologic changes, comorbidities and polypharmacy were the most widely researched. Inaccurate decision-making and poor early identification of major injuries were identified as potentially influencing patient outcomes. More research is required into paramedic knowledge of geriatric care & ageing changes and the potential impact of paramedic care. Conclusion: This is the first study reviewing the published evidence on prehospital trauma care for older patients and identifying research priorities for future research. This review has identified the prehospital triage for older trauma victims and studies of paramedic knowledge of older trauma care as key priorities. Investigating and understanding these can improve providing prehospital care of the older patient with injuries for positive patient outcomes.